Proprioceptive Neuromuscular Facilitation compared to usual resistance exercise therapy in individuals with knee osteoarthritis: a randomized clinical trial protocol (Research, Society and Development, 2022)
Background/Aims: Knee osteoarthritis (KOA) is characterized by functional impairment in performing of daily life activities. Proprioceptive Neuromuscular Facilitation (PNF) is a treatment concept that recommends performing exercises within a context of functionality. To develop a protocol to evaluate the efficacy of (PNF) compared to conventional physiotherapy (CPT group) on pain reduction and improvement in physical functioning and quality of life in individuals with KOA. Methods: A protocol for a randomized controlled trial was proposed to evaluate the effectiveness of the PNF protocol in pain reduction, improvement physical functioning, quality of life and evaluation of adverse effects, according Consolidated Standards of Reporting Trials. Participants will be randomly assigned (1:1) to PNF or CPT group and twelve weekly sessions will be carried out for three months. To assess primary outcome measures are knee pain severity (Numeric Rating Scale) and physical functioning (The Western Ontario and McMaster Universities questionnaire). The outcomes will be performed at baseline, 12th session (6 weeks), 24th session (12 weeks) and three-month follow-up. Intention-to-treat will be performed. Results: A PNF protocol was developed for KOA, consisting of seven illustrated exercises. Biomechanical objectives, observations, positions of individuals and therapists, load progression, PNF principles, procedures and techniques have been described. Conclusion: The detailed elaboration of a physical therapy treatment protocol based on the PNF-concept allows a treatment approach based on the principles of learning and motor control, favoring the mitigating and improving physical functioning and quality of life of the individuals with KOA.